The value of routine radiographic follow up in the postoperative management of canine medial patellar luxation. Issue 3 (10th January 2023) - Brincin, Charlie; Payne, Dylan J. L.; Grierson, James; Wood, Philippa; Robinson, William P.; Giustino, Vincenza S.; O' Sullivan, Joseph; Pilati, Filipo; Karydas, Stavros; Keeley, Ben; Bright, Steve; Bobis‐Villagra, Diego; et al.
Abstract: Objective: To determine the influence of radiographic examination on the recommendations made at the time of planned re‐evaluation of dogs after medial patellar luxation (MPL) surgery. Study design: Retrospective multi‐institutional case series. Animals: Client‐owned dogs ( N  = 825) that underwent MPL surgery. Methods: Records of 10 referral institutions were searched for dogs that had been treated surgically for unilateral MPL and underwent a planned follow‐up visit, including radiographs. The frequency of, and reasons for, changes in further recovery recommendations were investigated. Results: Follow up was performed at a median of 6 (range, 4‐20) weeks postoperatively. Isolated radiographic abnormalities were identified in 3.3% (27/825) of dogs following MPL surgery and led to a change in recommendations in 3% (13/432) of dogs that were presented without owner or clinician concerns. Lameness, administration of analgesia at follow up, and history of unplanned visits prior to routine re‐examination were associated with a change in postoperative plan ( P  < .001). In the absence of owner and clinician concerns, the odds of having a change in convalescence plans were not different, whether or not isolated radiographic abnormalities were present ( P  = .641). Conclusion: Routine radiographs at follow up did not influence postoperative management of most dogs after MPL surgery in the absence of abnormalities on clinical history or orthopedic examination. Clinical significance: Dogs that were presented for routine follow up after unilateral MPL surgery without owner concerns, lameness, analgesic treatment or a history of unplanned visits, and for which examination by a surgical specialist was unremarkable, were unlikely to benefit from radiographs.